Needles in Hay II: Detecting Cardiac Pathology by the Pediatric Chest Pain Standardized Clinical Assessment and Management Plan. (26th February 2016) - Kane, David A.; Friedman, Kevin G.; Fulton, David R.; Geggel, Robert L.; Saleeb, Susan F.
Abstract: Objectives: To determine if patients evaluated using the pediatric chest pain standardized clinical assessment and management plan (SCAMP) in cardiology clinic were later diagnosed with unrecognized cardiac pathology, and to determine if other patients with cardiac pathology not enrolled in the SCAMP would have been identified using the algorithm. Study Design: Patients 7–21 years of age, newly diagnosed with hypertrophic or dilated cardiomyopathy, coronary anomalies, pulmonary embolus, pulmonary hypertension, pericarditis, or myocarditis were identified from the Boston Children's Hospital (BCH) cardiac database between July 1, 2010 and December 31, 2012. Patients were cross‐referenced to the SCAMP database or retrospectively assessed with the SCAMP algorithm. Results: Among 98 patients with cardiac pathology, 34 (35%) reported chest pain, of whom 10 were diagnosed as outpatients. None of these patients were enrolled in the SCAMP because of alternate chief complaints (n = 4) or referral to BCH for management of the new diagnosis (n = 6). Each of these patients would have had an echocardiogram recommended by retrospective application of the SCAMP algorithm. Two other patients with cardiac pathology were among the 1124 patients assessed by the SCAMP. One patient initially diagnosed with noncardiac chest pain presented 18 months later and was diagnosed with myocarditis as an inpatient. One patient seen initially in the emergency department was subsequently diagnosed with pericarditis as an outpatient. Conclusions: Patients assessed by the chest pain SCAMP at BCH were not later diagnosed with cardiac pathology that was missed at the initial encounter. Nonenrolled outpatients with cardiac pathology and chest pain would have been successfully identified with the SCAMP algorithm.